Jewish Biblical Interpretation and Cultural Exchange : Comparative Exegesis in Context - Stern, David, 1949-; Dohrmann, Natalie B. (Book collections on Project MUSE., 2008)
Biblical interpretation is not simply study of the Bible's meaning. This volume focuses on signal moments in the histories of scriptural interpretation of Judaism, Christianity, and Islam from the ancient period to the early modern, and shows how deeply intertwined these religions have always been.